Incentive contracts and elections for politicians with multi-task problems - Gersbach, Hans; Liessem, Verena (SSRN, 2004)
We consider a model with a politician facing a multi-task problem while in office. The reelection mechanism distorts the allocation of effort in favor of tasks whose outcomes can be measured more precisely than others. We show that a hierarchy of elections and incentive contracts can alleviate this inefficiency, although the incentive contracts need to be based on the same information available to the voters at reelection date
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments September 2003 erstellt